RSK-dependent 14-3-3 interactions - Saha, Madhurima (International Journal of Research in Medical Sciences, 2017)
14-3-3 proteins were identified as abundant proteins from bovine brain homogenates. They eluted at the 14th fraction from a two-dimensional DEAE-cellulose chromatography column and were the 3.3 band on the subsequent gel electrophoresis.<a title="Moore, 1972 #36" href="file:///C:/Users/indias/Google%20Drive/Medip%20Academy/IJRMS/IJRMS%20Volume%205%20Issue%202/Paging%20IJRMS%20Vol%205%20Issue%202%20February%202017%20IJRMS/74%20740-741/IJRMS-2016-12-1217%20Letter%20to%20the%20editor.docx#_ENREF_1">1 14-3-3s were also given different names according to their novel roles in different organisms ranging from plants to animals as reviewed by Aitken.<a title="Aitken, 2006 #6" href="file:///C:/Users/indias/Google%20Drive/Medip%20Academy/IJRMS/IJRMS%20Volume%205%20Issue%202/Paging%20IJRMS%20Vol%205%20Issue%202%20February%202017%20IJRMS/74%20740-741/IJRMS-2016-12-1217%20Letter%20to%20the%20editor.docx#_ENREF_2">2 Physiologically, these are 30kDa acidic proteins and modulate other proteins in signal transduction pathways by binding to specific phospho-serine/threonine target motifs. The two highly preferred motifs recognized by 14-3-3 on their target proteins are R[S/Φ][+]pS/TXP (mode 1) and RX[S/Φ][+]pS/TXP (mode 2) where pS/T means phosphorylated serine or threonine, Φ means an aromatic residue, + is a basic residue and X is any type of an amino acid with a preference for Leu, Glu, Ala, Met.<a title="Obsil, 2011 #37" href="file:///C:/Users/indias/Google%20Drive/Medip%20Academy/IJRMS/IJRMS%20Volume%205%20Issue%202/Paging%20IJRMS%20Vol%205%20Issue%202%20February%202017%20IJRMS/74%20740-741/IJRMS-2016-12-1217%20Letter%20to%20the%20editor.docx#_ENREF_3">3 The regulation of multiple oncogenic proteins has spotlighted 14-3-3 as the central point of various signaling cues which govern cell proliferation, growth and tumor suppression.<a title="Wilker, 2004 #38" href="file:///C:/Users/indias/Google%20Drive/Medip%20Academy/IJRMS/IJRMS%20Volume%205%20Issue%202/Paging%20IJRMS%20Vol%205%20Issue%202%20February%202017%20IJRMS/74%20740-741/IJRMS-2016-12-1217%20Letter%20to%20the%20editor.docx#_ENREF_4">4 There are seven distinct isoforms in mammals (ζ, β, γ, η, σ, τ and ε), fifteen in plants and two each in D. melanogaster and C. elegans.<a title="Dougherty, 2004 #39" href="file:///C:/Users/indias/Google%20Drive/Medip%20Academy/IJRMS/IJRMS%20Volume%205%20Issue%202/Paging%20IJRMS%20Vol%205%20Issue%202%20February%202017%20IJRMS/74%20740-741/IJRMS-2016-12-1217%20Letter%20to%20the%20editor.docx#_ENREF_5">5 They exist as homodimers and except for the sigma isoform which exists as heterodimers within the cell and can bind to more than one protein due to the dimerization of the monomers.12